Smart energy systems - Tsukasa Yoshida; He Sun; Ajit Khosla (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Some aspects of renewable and smart energy systems have been considered. Comparison of different renewable energy sources such as offshore wind, land-based wind, biomass, PV Solar, hydro-electric and geothermal has been demonstrated. The shift from solar cells (energy production) to batteries (energy storage) is the mainstream in the modern power supply. One of the promising technologies for the storage station is a redox flow battery (RFB). RFBs can also be used as the power sources for electric vehicles. There is another type of battery, the so-called metal-air batteries (such as Zn-air, Al-air), which are the smartest energy systems for mobile applications.